2011
DOI: 10.1007/s10815-011-9542-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary male infertility in Izmir/Turkey: a cytogenetic and molecular study of 187 infertile Turkish patients

Abstract: Purpose To detect somatic cytogenetic abnormalities and AZF microdeletions in a sample of 187 Turkish infertile men to determine the frequencies and the characteristics of our primary male infertility data in order to perform appropriate genetic counseling. Methods This study included 187 infertile men. Chromosomal studies and screening of AZF deletions was performed by multiplex polymerase chain reaction (PCR) analysis using the Y Chromosome Deletion Detection System.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
1
16
1
1
Order By: Relevance
“…Deletions of the different AZF regions occured with different frequency. Confirming previous data [1,15,26], our findings showed that classical AZFc deletions represented the most frequent finding (54.17% of deletions in our cases), followed by the AZFbc region (18.75%), AZFb (10.42%) and AZFa (9.03%). Our data revealed that there was a slightly higher frequency of the AZFa and AZFb microdeletions in infertile patients than previous studies [14,26], which was mainly due to a high rate of partial deletions in AZFa region.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Deletions of the different AZF regions occured with different frequency. Confirming previous data [1,15,26], our findings showed that classical AZFc deletions represented the most frequent finding (54.17% of deletions in our cases), followed by the AZFbc region (18.75%), AZFb (10.42%) and AZFa (9.03%). Our data revealed that there was a slightly higher frequency of the AZFa and AZFb microdeletions in infertile patients than previous studies [14,26], which was mainly due to a high rate of partial deletions in AZFa region.…”
Section: Discussionsupporting
confidence: 92%
“…Subsequently, numerous studies on the association of the Y chromosome AZF microdeletion with male infertility were reported. These studies revealed that Y chromosome microdeletions ranged from 1% to 55% among infertile men with azoospermia or severe oligozoospermia [1,13,18,37]. We investigated AZF microdeletion in 1,333 infertile patients and found the total prevalence of AZF microdeletion was 10.80%.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 32 selected studies 14 are from descriptive [1, 2, 4, 13, 24, 27-29, 31, 32, 34-37], 08 are cross-sectional [3,5,17,18,21,25,26,33], 05 are experimental [7,12,19,20,38], 03 are case reports [22,30,39] and 02 are case-control studies [10,23]. Studies have good methodological accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of factors related to male is between 30-50% [5]. Failures in spermatogenesis are among the main reasons with 50% of cases [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation